Addressing Household Cooking Fuel Options in Nigeria. Issue 1 (April 2021) - Nnaji, M; Eze, A A; Uzoma, C C; Nnaji, C E
Abstract: Households constitute the most significant sector in energy consumption in Nigeria. A plethora of energy source endowments exists to fulfill this demand. However, addressing the cooking fuels need arises due to issues relating to the economy, health and the environment. This necessitates empirical evidence to effect national efficient choice making and policy to entrench modern energy services. Mixed methods of analysis were employed to assess the economics of household cooking fuel choice, and policy option that would enhance productivity and inform future policy for rapid economic growth and environmental sustainability in Nigeria. Given the study findings from survey, the best alternative household energy for cooking in Nigeria is liquefied petroleum gas (LPG). Unimproved solid fuel use contributing 69.1% and 68.6% clearly dominates the household energy cooking choice over the five year period 2013 and 2018 despite its deleterious effects on the health, productivity and environmental sustainability of the economy. Government support and policy should be used to address the existing energy trilemma of productivity growth, access and security, and environmental sustainability to the economy by effectively utilizing the natural gas (LPG) endowments of Nigeria that was little used of as household cooking fuel choice in the ratio of 2.3% and 14.0% over the same period.